Structural-metamorphic imprint on part of the Namaqua mobile belt in Southwest Africa - Blignault, H J (Department of Geological Sciences, 2023)
The cross-section of the part of the Namaqua Mobile Belt investigated, comprises tectonic domains differing in structural and metamorphic character. The upper-crustal Richtersveld Province is separated from the lower-crustal central zone by a marginal zone across which there is a sharp increase in P and T. A continuous prograde metamorphic zonation is established which is bounded on the low-grade side by the 'hornblende in' reaction and includes with increasing grade 'muscovite+ chlorite out', andalusite/sillimanite inversion, minimum melt line, •·epidote out', 'K-felspar + sillimanite in' and a brown hornblende zone. The PT conditions inferred for the K-felspar + sillimanite zone is in the order of 6 kb and 740°c. This metamorphic zonation is defined by the metamorphic peak at any one point and is associated with the early structures. Subsequent deformations indicate a continuous retrogression. The early kinematic event includes at least two phases of coaxial and coplanar folding giving rise to the main planar fabric which is interpreted as a shear surface. It is concluded that the first kinematic event constitutes a thrust regime. The latE kinematic event is represented in the central zone by two phases of macroscopic folding which yielded basin and dome structures. To accommodate the resultant lateral shortening in the central zone, the Kanabeam shear zone developed between the central zone and the more upper-crustal domains where the late phase folding is not developed. Two discrete magmatic events, yielding differentiated intrusive are closely related in time to the early kinematic event. These intrusives underlie at least 50 per cent of the area. The Vioolsdrif Suite (1900 Ma) is genetically related to the Orange River volcanics. The intersected volcanics (2000 Ma) and intrusives form the Vioolsdrif igneous complex which is correlated with the grey gneiss of the lower-crustal domains. In the high-grade central zone aluminous paragneisses structurally overlie the grey gneisses and are interpreted as a mudstone/wacke sequence. The early kinematic event, associated with thrusting, the main metamorphism and extensive intrusion, constitutes the main phase of the Namaqua tectogenesis which connnenced at least at about 1900 Ma. The late kinematic event is associated with lateral movement and shortening during the waning stages of the Namaqua tectogenesis at about 1000 Ma.